Look-up table predistorter based on non-iterative algorithm and indirect learning architecture for TWTA - WANG Yong1; XIANG Xin1; 2 (Tongxin xuebao)
Based on look-up table （LUT） and indirect learning architecture, a baseband predistorter was proposed for travel wave tube amplifier （TWTA）. Non-iterative method for capturing parameters of the predistorter was realized by the means of linear increasing periodic training sequence and distortion estimation algorithm. Compared with the conven-tional predistorter based on LUT, the proposed predistorter could process distortion data offline without minimum cost function to update the LUT, which lowers the processing requirement of the predistortion system and avoids convergence problem of adaptive algorithm. Simulation results show that the predistorter can reduce in-band distortion and spectrum regrowth greatly introduced by the nonlinear effects of TWTA.